Early specialist palliative care on quality of life for malignant pleural mesothelioma: a randomised controlled trial. Issue 4 (19th January 2019) - Brims, Fraser; Gunatilake, Samal; Lawrie, Iain; Marshall, Laura; Fogg, Carole; Qi, Cathy; Creech, Lorraine; Holtom, Nicola; Killick, Stephanie; Yung, Bernard; Cooper, David; Stadon, Louise; et al.
Abstract : Purpose: Malignant pleural mesothelioma (MPM) has a high symptom burden and poor survival. Evidence from other cancer types suggests some benefit in health-related quality of life (HRQoL) with early specialist palliative care (SPC) integrated with oncological services, but the certainty of evidence is low. Methods: We performed a multicentre, randomised, parallel group controlled trial comparing early referral to SPC versus standard care across 19 hospital sites in the UK and one large site in Western Australia. Participants had newly diagnosed MPM; main carers were additionally recruited. Intervention: review by SPC within 3 weeks of allocation and every 4 weeks throughout the study. HRQoL was assessed at baseline and every 4 weeks with the European Organization for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core 30. Primary outcome: change in EORTC C30 Global Health Status 12 weeks after randomisation. Results: Between April 2014 and October 2016, 174 participants were randomised. There was no significant between group difference in HRQoL score at 12 weeks (mean difference 1.8 (95% CI −4.9 to 8.5; p=0.59)). HRQoL did not differ at 24 weeks (mean difference −2.0 (95% CI −8.6 to 4.6; p=0.54)). There was no difference in depression/anxiety scores at 12 weeks or 24 weeks. In carers, there was no difference in HRQoL or mood at 12 weeks or 24 weeks, although there was a consistent preference for care, favouring the intervention arm. Conclusion: There is no role for routine referral to SPC soon after diagnosis of MPM for patients who are cared for in centres with good access to SPC when required. Trial registration number: ISRCTN18955704 .